Membangun Iklim Sekolah Ramah Anak: Program Pencegahan Perundungan di SDN 010029 Desa Perkebunan Sukaraja - Rahmadani, Elfira; Lidiana Permata Sari, Putri; Azhari, Rahmad; Pradana Tamba, Andre; Syahida Siregar, Hanadia; Roma Utami, Naila; Sonita, Elvina (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: Bullying in Indonesian elementary schools continues to pose a significant threat to students' safety and well-being. In order to improve anti-bullying literacy, increase social awareness, and promote a secure and welcoming school environment, the "Building a Child-Friendly School Climate: Bullying Prevention Program in Elementary Schools" program was put into place. Thirty-two pupils in grades IV–VI participated in the one-day participatory activity at SDN 010029 Perkebunan Sukaraja Village, Asahan Regency. Ice-breaking, conversation, role-playing, storytelling, poster-making, and introspection were among the techniques employed. A Likert-scale questionnaire evaluation revealed an average overall score of 3.75 (very good category), with material understanding (3.81) and applicability to school life (3.78) showing the greatest signs.Students' awareness, empathy, and bravery in confronting bullying increased, according to qualitative data. The activity's outcomes show that a practical, experience-based approach is successful in fostering a school climate that is kid-friendly and establishing anti-bullying ideals. From a scientific perspective, this program helps primary schools create models of violence prevention and character education that align with the national PPKSP and Child-Friendly Schools regulations. It is hoped that this program will be adopted as a routine school activity. Keywords: anti-bullying literacy; school climate; bullying; child-friendly schools; elementary education Abstrak: Perundungan (bullying) di sekolah dasar masih menjadi tantangan serius bagi kesejahteraan dan rasa aman peserta didik di Indonesia. Program Membangun Iklim Sekolah Ramah Anak: Program Pencegahan Perundungan di Sekolah Dasar dilaksanakan untuk memperkuat literasi anti-perundungan, meningkatkan kesadaran sosial, dan menumbuhkan budaya sekolah yang aman serta inklusif. Kegiatan dilaksanakan secara partisipatif selama satu hari di SDN 010029 Desa Perkebunan Sukaraja, Kabupaten Asahan, dengan melibatkan 32 siswa kelas IV–VI. Metode yang digunakan mencakup ice-breaking, diskusi, storytelling, permainan peran, pembuatan poster, dan refleksi. Evaluasi melalui angket skala Likert menunjukkan rata-rata skor keseluruhan sebesar 3,75 (kategori sangat baik), dengan indikator tertinggi pada keterpahaman materi (3,81) dan relevansi dengan kehidupan sekolah (3,78). Data kualitatif memperlihatkan peningkatan kesadaran, empati, dan keberanian siswa menolak perundungan. Hasil kegiatan ini membuktikan bahwa pendekatan berbasis pengalaman langsung efektif dalam menanamkan nilai-nilai anti-perundungan dan memperkuat iklim sekolah yang ramah anak. Secara ilmiah, program ini berkontribusi pada pengembangan model pendidikan karakter dan pencegahan kekerasan di sekolah dasar yang sejalan dengan kebijakan nasional PPKSP dan Sekolah Ramah Anak. Program ini diharapkan diadopsi sebagai kegiatan rutin sekolah. Keterbatasan kegiatan yang dilaksanakan satu hari masih menyisakan ruang untuk penguatan program secara berkelanjutan melalui aktivasi Satgas PPKSP. Kata kunci: Perundungan; Iklim Sekolah; Sekolah Ramah Anak; Literasi Anti-Perundungan; Pendidikan Dasar